Sex differences in the structural rich-club connectivity in patients with Alzheimer’s disease - Kim, Soo-Jong; Bae, Youn Jung; Park, Yu Hyun; Jang, Hyemin; Kim, Jun Pyo; Seo, Sang Won; Seong, Joon-Kyung; Kim, Geon Ha (Frontiers in Aging Neuroscience, 2023)
Background & Objectives: Alzheimer's disease (AD) is more prevalent in women than in men; however, there is a discrepancy in research on sex differences in AD. The human brain is a large-scale network with hub regions forming a central core, the rich-club, which is vital to cognitive functions. However, it is unknown whether alterations in the rich-clubs in AD differ between men and women. We aimed to investigate sex differences in the rich-club organization in the brains of patients with AD. Methods: In total, 260 cognitively unimpaired individuals with negative amyloid positron emission tomography (PET) scans, 281 with prodromal AD (mild cognitive impairment due to AD) and 285 with AD dementia who confirmed with positive amyloid PET scans participated in the study. We obtained highresolution T1-weighted and diffusion tensor images and performed network analysis. Results: We observed sex differences in the rich-club and feeder connections in patients with AD, suggesting lower structural connectivity strength in women than in men. We observed a significant group-by-sex interaction in the feeder connections, particularly in the thalamus. In addition, the connectivity strength of the thalamus in the feeder connections was significantly correlated with general cognitive function in only men with prodromal AD and women with AD dementia. Conclusions: Our findings provide important evidence for sex-specific alterations in the structural brain network related to AD.